Influence of a nanotwinned, nanocrystalline microstructure on aging of a Ni-25Mo-8Cr superalloy. (1st September 2018) - Emigh, Megan G.; McAuliffe, Rebecca D.; Chen, Changqiang; Mabon, James C.; Weihs, Timothy; Hemker, Kevin J.; Shoemaker, Daniel P.; Krogstad, Jessica A.
Abstract: Precipitation pathways in many nickel-based superalloys are highly complex and in some cases proceed very slowly. This behavior has hampered their introduction into some novel application spaces ranging from microelectromechanical systems (MEMS) to protective coatings, wherein their high temperature strength and oxidation resistance would otherwise be highly desirable. In this investigation, the microstructure of Ni-25Mo-8Cr superalloy thin films prepared via direct current magnetron sputtering (DCMS) is shown to be key to manipulating and understanding phase transformations. Specifically, the columnar, highly textured, and nanotwinned grains are shown to facilitate precipitation of the equilibrium DOa (Ni3 Mo) phase during a mild heat treatment. Conversely, elimination of the nanotwins through a two-step heat treatment leads to precipitation of metastable Ni2 (Mo, Cr) (isomorphous with Pt2 Mo and Ni2 Cr) precipitates. The straightforward capacity to select one of several possible phase transformation pathways presents an opportunity to create precisely tuned microstructures specific to the desired application, while simultaneously providing unprecedented insight on these complex phase transformations. Graphical abstract: Image 1